Coordinated regulation of heterochromatic genes in Drosophila melanogaster males. - Deng, X.; Koya, S.K.; Kong, Y.; Meller, V.H. (Genetics, 2009)
Dosage compensation modifies the chromatin of X-linked genes to assure equivalent expression in sexes with unequal X chromosome dosage. In Drosophila dosage compensation is achieved by increasing expression from the male X chromosome. The ribonucleoprotein dosage compensation complex (DCC) binds hundreds of sites along the X chromosome and modifies chromatin to facilitate transcription. Loss of roX RNA, an essential component of the DCC, reduces expression from X-linked genes. Surprisingly, loss of roX RNA also reduces expression from genes situated in proximal heterochromatin and on the small, heterochromatic fourth chromosome. Mutation of some, but not all, of the genes encoding DCC proteins produces a similar effect. Reduction of roX function suppresses position effect variegation (PEV), revealing functional alteration in heterochromatin. The effects of roX mutations on heterochromatic gene expression and PEV are limited to males. A sex-limited role for the roX RNAs in autosomal gene expression was unexpected. We propose that this reflects a difference in the heterochromatin of males and females, which serves to accommodate the heterochromatic Y chromosome present in the male nucleus. roX transcripts may thus participate in two distinct regulatory systems that have evolved in response to highly differentiated sex chromosomes: compensation of X-linked gene dosage and modulation of heterochromatin.